Operative repair of acute Achilles tendon rupture does not give superior patient-reported outcomes to nonoperative management: results of a randomized controlled trial at a minimum of 13 years' follow-up. (July 2020) - Maempel, Julian F.; Clement, Nicholas D.; Wickramasinghe, Neil R.; Duckworth, Andrew D.; Keating, John F.
Abstract : Aims: The aim was to compare long-term patient-reported outcome measures (PROMs) after operative and nonoperative treatment of acute Achilles tendon rupture in the context of a randomized controlled trial. Methods: PROMs including the Short Musculoskeletal Function Assessment (SMFA), Achilles Tendon Total Rupture Score (ATRS), EuroQol five-dimension (EQ-5D), satisfaction, net promoter score and data regarding re-rupture, and venous thromboembolic rates were collected for patients randomized to receive either operative or nonoperative treatment for acute Achilles tendon rupture in a previous study. Of the 80 patients originally randomized, 64 (33 treated surgically, 31 nonoperatively) patients were followed up at a mean of 15.7 years (13.4 to 17.7). Results: There was no statistically significant difference between operatively and nonoperatively treated patients, in SMFA Dysfunction Index (median 1.56 (interquartile range (IQR) 0 to 5.51) vs 1.47 (IQR 0 to 5.15); p = 0.289), SMFA Bother Index (2.08 (IQR 0 to 12.50) vs 0.00 (IQR 0 to 6.25); p = 0.074), ATRS (94 (IQR 86 to 100) vs 95 (IQR 81 to 100); p = 0.313), EQ-5D-5L (1 (IQR 0.75 to 1) vs 1 (IQR 0.84 to 1); p = 0.137) or EQ-5D health today visual analogue score (85 (IQR 72.5 to 95) vs 85 (IQR 8 to 95); p = 0.367). There was no statistically significant difference between operative and nonoperative groups in terms of satisfaction (84% vs 100%; p = 0.119) or willingness to recommend treatment to friends or family (79% vs 87%; p = 0.255). Four nonoperative patients and two in the operative group sustained a re-rupture (p = 0.306). Conclusion: Both patient groups reported good results at long-term follow-up. The findings give no evidence of superior long-term patient reported outcomes (as measured by the SMFA) for surgical treatment over nonoperative treatment. There was no demonstrable difference in other patient reported outcome measures, satisfaction, or re-rupture rates at long-term follow-up. Cite this article: Bone Joint J 2020;102-B(7):933–940.